Even in translation, Richter's 'science' unimpressive - Luzuriaga, J. (AIP Publishing, 2005)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina